2018
DOI: 10.1002/anie.201801110
|View full text |Cite
|
Sign up to set email alerts
|

Synthesis of (−)‐Hebelophyllene E: An Entry to Geminal Dimethyl‐Cyclobutanes by [2+2] Cycloaddition of Alkenes and Allenoates

Abstract: The first synthesis of hebelophyllene E is presented, along with assignment of its previously unknown relative configuration through synthesis of epi-ent-hebelophyllene E. Development of a catalytic enantioselective [2+2] cycloaddition of alkenes and allenoates provides access to the required chiral geminal dimethylcyclobutanes. Key to its success is the identification of a novel oxazaborolidine catalyst which promotes the cycloaddition in high enantioselectivities with good functional-group tolerance (9 examp… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
6
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 36 publications
(6 citation statements)
references
References 50 publications
0
6
0
Order By: Relevance
“…We later found that a more accessible thiobenzyl allenoate also exhibited comparable reactivity and enantioselectivity and, in some cases, higher E/Z selectivity (compare 3.13 to 3.14 ) . Oxazaborolidine 3.15 with a 3,5-(CF 3 ) 2 –C 6 H 3 backbone instead of Ph was found to be more selective when reacting with trisubstituted alkenes and activated alkenes. , γ-Dimethyl-substituted allenoates were also tolerated in reactions with unactivated alkenes (products 3.19 and 3.20 ).…”
Section: Enantioselective [2 + 2] Cycloadditions Of Allenoatesmentioning
confidence: 99%
See 2 more Smart Citations
“…We later found that a more accessible thiobenzyl allenoate also exhibited comparable reactivity and enantioselectivity and, in some cases, higher E/Z selectivity (compare 3.13 to 3.14 ) . Oxazaborolidine 3.15 with a 3,5-(CF 3 ) 2 –C 6 H 3 backbone instead of Ph was found to be more selective when reacting with trisubstituted alkenes and activated alkenes. , γ-Dimethyl-substituted allenoates were also tolerated in reactions with unactivated alkenes (products 3.19 and 3.20 ).…”
Section: Enantioselective [2 + 2] Cycloadditions Of Allenoatesmentioning
confidence: 99%
“…31 The synthesis commenced with trisubstituted alkene 4.1 that was prepared on decagram scale from t-Bu-acetoacetate. 28 Key to the synthesis of 4.3 were a kinetic resolution of 4.2 and diastereoselective addition of vinylMgBr (Scheme 4A). Alkene 4.3 was well tolerated in the enantioselective [2 + 2] cycloaddition to give 4.4 in 52% yield after separation of the Z/E mixture.…”
Section: Of Ketenesmentioning
confidence: 99%
See 1 more Smart Citation
“…We envisioned that a highly reactive cyclobutenone with better stability would provide a practical approach to access enantioenriched bicyclo[4.2.0]octane derivatives. Herein we report our work on unique reactivity of 3-methoxycarbonylcyclobutenone 2 as dienophile in enantioselective Diels-Alder reaction under the catalysis of chiral oxazaborolidinium ion [12,13] (Scheme 1 b).…”
mentioning
confidence: 99%
“…The 3.2.0 bicyclic unit is found in a myriad of natural products and functional bioactive molecules. 1 Several of these examples feature an alkene motif that suggests sealing the four-membered ring via an intramolecular [2 + 2] cycloaddition from an enallene. 2 However, the allene functionalization presents regiochemical challenges ( Scheme 1 ).…”
mentioning
confidence: 99%